2019
DOI: 10.1186/s12014-019-9226-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic characterization of lung tissue in idiopathic pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive, eventually fatal disease. IPF is characterized by excessive accumulation of the extracellular matrix (ECM) in the alveolar parenchyma and progressive lung scarring. The pathogenesis of IPF and whether the ECM involved in the process remain unknown.MethodsTo identify potential treatment target and ECM associated proteins that may be involved in the development of IPF, we employed isobaric tag for relative and absolute quantitation (iTRAQ) combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 51 publications
6
39
0
1
Order By: Relevance
“…This approach utilizes multi-steps to enrich for ECM proteins and we report that 11.1% of the proteins detected are ECM components. This is in accord with studies utilizing human lung specimens where the percentage of ECM components detected are reported as 5.4% [34], 7.2% [35], and 8.2% [36]; in mouse lungs, 5.2% is reported [37]. The protein gene names for these regions are shown in Fig.…”
Section: The Ecm Comprising Morphologically Normal Human Lung Alveolisupporting
confidence: 89%
“…This approach utilizes multi-steps to enrich for ECM proteins and we report that 11.1% of the proteins detected are ECM components. This is in accord with studies utilizing human lung specimens where the percentage of ECM components detected are reported as 5.4% [34], 7.2% [35], and 8.2% [36]; in mouse lungs, 5.2% is reported [37]. The protein gene names for these regions are shown in Fig.…”
Section: The Ecm Comprising Morphologically Normal Human Lung Alveolisupporting
confidence: 89%
“…Isobaric tag for relative and absolute quantitation (iTRAQ) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to analyze proteomic changes in lung tissue of IPF patients and controls [53]. From more than 4000 proteins analyzed, 600 were founded altered (455 upregulated and 207 downregulated) confirming previous results on extracellular matrix overexpression and defining new involved proteins.…”
Section: Proteomic Analysis In Idiopathic Pulmonary Fibrosissupporting
confidence: 59%
“…From more than 4000 proteins analyzed, 600 were founded altered (455 upregulated and 207 downregulated) confirming previous results on extracellular matrix overexpression and defining new involved proteins. Among these, several collagens, glycoproteins, proteoglycans, and secretory and regulatory factor matrisomes were identified and validated by Western blotting, confirming the role of collagen 1, cathepsin B, AGR-2, galectin-7, HSP90α, and HSP90β [53]. In another study, functional proteomics was used to analyze differences in four diseases (idiopathic pulmonary fibrosis, sarcoidosis, systemic sclerosis, and pulmonary Langerhans sclerosis).…”
Section: Proteomic Analysis In Idiopathic Pulmonary Fibrosismentioning
confidence: 79%
“…Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and fatal interstitial lung disease (ILD) [1], characterized by an increase of fibroblast proliferation, an excessive extracellular matrix (ECM) deposition [2], and distortion of lung architecture, eventually leading to respiratory failure [3]. To date, limited treatment options are available, and prognosis remains still poor [4]. Although the etiology of this disease is not completely known, some studies have shown how environmental factors (smoking and exposure to toxic agents), age, and genetic factors represent the main risk factors for IPF onset [5].…”
Section: Introductionmentioning
confidence: 99%